Caracterização reo-óptica da interação entre desenovelamento e desenrosco de cadeias poliméricas em fluxo cisalhante - Tambolim, Murilo (2024)
Rheo-optical studies involve monitoring the flow of polymers by measuring their optical properties. In the case of pure polymeric fluids, flow birefringence can be used to quantify the molecular chain orientation. This study conducted flow birefringence experiments using atactic homopolymer pure polystyrene under various shear rates, shear cycles, and temperatures. These experiments were conducted using a polarized light optical microscope coupled with a controlled shear system and a transmitted light optical detector. The research focused on analyzing the degree of chain orientation and its correlation with the dynamics of chain uncoil, disentanglement and recoil. The expected increase in the orientation level as a function of the increase in the shear rate due to the chain uncoiling was confirmed. Over time, the degree of chain orientation decreased, primarily associated with chain disentanglement followed by recoiling. Notably, disentanglement was observed to be irreversible, whereas uncoiling and recoiling were reversibleprocesses. Based on these observations, a model was proposed to depict these molecular dynamics.